HMM-based profiling identifies the binding to divalent cations and nucleotides as common denominators of suramin targets - Hauser, Dennis A.; Mäser, Pascal (Frontiers in Drug Discovery, 2023)
Suramin is one of the pharmacopeia's most promiscuous drugs. Originally developed for African trypanosomiasis, suramin was also used for onchocerciasis and it has been proposed as an anticancer agent, antiviral drug, therapy for arthritis, autism, and antidote for snake bites. Target proteins of suramin have been described from different species. Here we identify the common motifs among these various targets, aiming to explain the promiscuous nature of suramin. We have searched for suramin target proteins in the literature and in chemical databases. Applying rigorous inclusion criteria, a list of 44 diverse proteins was assembled with experimental evidence for direct interaction with, and inhibition by, suramin. Hidden Markov model-based target profiling was performed by running the full set of Pfam protein family domains against these proteins. Common denominators were identified by mapping the identified Pfam domains to molecular function gene ontology terms. This in silico pipeline identified nucleotide binding, nucleic acid binding, and binding to divalent cations as the most common denominators of the suramin targets. Our results suggest that the extraordinary polypharmacology of suramin may be caused by its ability to inhibit the interaction of proteins with nucleotides or nucleic acids and with divalent cations (Mg2+, Ca2+, Zn2+). Suramin is well known to inhibit nucleotide receptors and nucleic acid-binding enzymes. The association with divalent cations is new and might be key towards the design of better, more selective inhibitors.